علاقة الاستجابة الانفعالية السلبية بمخاوف الحضور لدى لاعبي الاحتياط بكرة القدم - الوتار، ناظم شاكر يوسف; رشيد، نوفل فاضل; صالح، محمد خير الدين (جامعة صلاح الدين, 2017)
هدفت هذه الدراسة إلى التعرف على الاستجابات الانفعالية السلبية ومخاوف الحضور الذاتي لدى لاعبي الاحتياط بكرة القدم في إقليم كوردستان العراق فضلا عن التعرف عل طبيعة العلاقة بين الاستجابات الانفعالية السلبية ومخاوف الحضور الذاتي لدى لاعبي الاحتياط بكرة القدم. استخدم الباحثون المنهج الوصفي لملاءمته لطبيعة البحث، تمثل مجتمع البحث من لاعبي كرة القدم البدلاء المشاركين في دوري إقليم كوردستان للموسم الرياضي (2015-2016) وبواقع (13) نادي والبالغ عددهم (172) لاعب تم اختيار عينة البحث بطريقة عمدية من لاعبي الأندية المشاركة بعد استبعاد عينة الثبات والبالغ عددهم (22) لاعبا، واستبعاد عينة التجربة الاستطلاعية والبالغ عددهم (24) واستبعاد اللاعبين الذين لم الذين لم يكملوا الإجابة عل المقاييس والبالغ عددهم (26) وبذلك بلغ أفراد عينة البحث (100) لاعبا واستخدم الباحثون مقياس الاستجابة الانفعالية السلبية ومقياس مخاوف الحضور الذاتي كأداتان للقياس في البحث وتم معالجة البيانات التي حصل عليها الباحثون باستخدام (الوسط الحسابي، الانحراف المعياري، قانون النسبة المئوية، معامل الارتباط البسيط (بيرسون)، قانون المتوسط الفرضي). نتوصل الباحثون الى الاستنتاجات الاتية : - ارتفاع درجة الاستجابات الانفعالية السلبية لدى لاعبي الاحتياط بكرة القدم . - ارتفاع درجة مخاوف الحضور الذاتي لدى لاعبي الاحتياط بكرة القدم. — ان استجابات اللاعبين الاحتياط الانفعالية الملبية ومخاوف الحضور الذاتي كانت نتيجة للافكار والمعتقدات الخاصة، بهم من خلال تفسيرهم للابعاد التنظيمة والشخصية، والتنافسية فضلا عن عن مخاوفهم المتعلقة بانطباعات الاخربن عنهم وهذا ما يؤكد الرابط بين المتغيرين.
The aim of this investigation is to realize the passive emotional responses and self-presence anxieties of football substitute players in the province of Kurdistan\ Iraq as well as the nature of the relationship among passive emotional responses and Self-Presentation Concerns of football substitute players. Researchers have used the descriptive method for being convenient with the nature of the research. The population of the research was represented by (172) football substitute players who participated in Kurdistan province tournament for the sport season (2015-2016) in the amount of (13) clubs. The sample of the research has been chosen from players belong to clubs that took part in the tournament according to a premeditated method after excluding (22) players that represent the sample of invariability, (24) players that represent the sample of the exploratory experiment and (26) players who were not able to complete the answers on the scales. Thus, the total number of the research sample has become (100) players. Researchers have applied two measurement tools in the research, the passive emotional response scale and self-presentation concerns scale. Data obtained by the researchers were handled through using (arithmetic mean, normative deviation, percentage law, Pearson's simple correlation coefficient and hypothetical mean law). Researchers have concluded the following: The degree of passive emotional responses of football substitute players has elevated The degree of self-presentation concerns of football substitute players has elevated Passive emotional responses and self-presence anxieties of football substitute players have resulted from their own ideas and beliefs through their interpretation of the organizational, personal and competitive dimensions as well as their anxieties related to other's impressions about them such that asserting the link between the two variables.
Keywords: علم النفس الرياضي -- التربية الرياضية -- كرة القدم